2022
DOI: 10.3389/fgene.2022.895211
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Severe COVID-19 Might Increase the Risk of Stroke: A Two-Sample Mendelian Randomization Study

Abstract: Aims: The causal relationship between COVID-19 infection and stroke has not yet been fully established. This study aimed to explore this causality using two-sample Mendelian randomization (MR).Materials and Methods: Genetic variants associated with COVID-19 infection and stroke were both obtained from genome-wide association study (GWAS) summary data. The single nucleotide polymorphisms (SNPs) were selected as instrumental variables. The standard inverse variance weighted (IVW) was primarily used to assess thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Summary statistics for stroke (40,585 cases and 406,111 controls) and ischemic stroke (34,217 cases and 406,111 controls) of European ancestry was obtained. [ 6 ] Additionally, the causal role of breast cancer on common etiological subtypes of ischemic stroke such as large artery atherosclerosis (4373 cases and 406,111 controls), cardioembolic stroke (7193 cases and 406,111 controls), and small-vessel stroke (5386 cases and 192,662 controls) was also evaluated. [ 7 ] Ischemic stroke subtypes were classified based on the Trial of Org 10172 in Acute Stroke Treatment criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Summary statistics for stroke (40,585 cases and 406,111 controls) and ischemic stroke (34,217 cases and 406,111 controls) of European ancestry was obtained. [ 6 ] Additionally, the causal role of breast cancer on common etiological subtypes of ischemic stroke such as large artery atherosclerosis (4373 cases and 406,111 controls), cardioembolic stroke (7193 cases and 406,111 controls), and small-vessel stroke (5386 cases and 192,662 controls) was also evaluated. [ 7 ] Ischemic stroke subtypes were classified based on the Trial of Org 10172 in Acute Stroke Treatment criteria.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] Notably, the risk of stroke appears to be notably elevated in patients who have experienced severe COVID-19. 4,6 However, existing studies have certain limitations that warrant further exploration. First, previous investigations have predominantly focused on examining the association between COVID-19 and stroke, with the causal relationship pertaining to each stroke subtype, including ischemic stroke (IS), large-artery atherosclerotic stroke (LAS), cardioembolic stroke (CES), and small-vessel stroke (SVS), remaining unknown.…”
Section: Several Observational and Mendelian Randomization (Mr)mentioning
confidence: 99%
“…studies have indicated the potential for individuals to experience long-term cardiovascular and cerebrovascular complications following recovery from severe COVID-19 infection. [3][4][5] Notably, the risk of stroke appears to be notably elevated in patients who have experienced severe COVID-19. 4,6 However, existing studies have certain limitations that warrant further exploration.…”
Section: Several Observational and Mendelian Randomization (Mr)mentioning
confidence: 99%